Analisis Pengelolaan Anggaran Dana Desa Berdasarkan Kebutuhan Masyarakat di Kapanewon Bambanglipuro Kabupaten Bantul Propinsi DIY - Eliya Isfaatun; Taufik Hidayat (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2022)
Village Funds according to Government regulation Number 6 of 2014 are funds sourced from the APBD for villages transferred through Regency/City Regional Budgets and Expenditures and used to finance government administration, development implementation, community development, and community empowerment. Village funds can play a major role in reducing the number of villages left behind if managed properly. This study aims to analyze the efficient and effective use of village funds in Kapanewon Bambanglipuro which consists of three villages, namely Sidomulyo Village, Mulyodadi Village, and Sumbermulyo Village. The analytical tool used in this research is the combination method (Mix Methods), which analyzes the target data, between the realization of expenditure and income by using the ratio of efficiency and effectiveness, and complements it with interview data. Data collection uses the Sequential Explanatory Design model, where the model is characterized by data collection and quantitative data analysis in the first stage, followed by qualitative data collection and analysis in the second stage, in order to strengthen the results of quantitative research conducted in the first stage. The results of this study indicate that the average level of efficiency of Village Fund management in Kapanewon Bambanglipuro Bantul Regency is 98% which meets the criteria of being less efficient, and the average level of effectiveness is 98%, including in the effective category. Keywords: Village funds, efficiency, effectiveness